The Relationship between Mental Toughness and Anxiety in Athletes: A Meta-Analysis Study - Islam, Syahrizal; Husein, Muhamad; Hasan, Baharuddin; Muti, Gilang Gemilang; Muti, Nabella Salsabila; Lembang, Melyani Taruk; Nubatonis, Jefrio Demitrimus; Kristiono, Aljawahir Agus; Taiar, Redha; Salacup, Vince Louisse D. (JSES : Journal of Sport and Exercise Science, 2025)
Purpose: This study was motivated by the importance of the role of psychological aspects, especially mental toughness, in supporting athletes' abilities when facing anxiety in a match. Materials and Methods: This study used a meta-analysis method. The search used the Publish and Publish application, with Google Scholar as the database. Literature searches from various sources used the keywords: "Mental Toughness", "Athlete Anxiety", "Competitive Anxiety", "Performance Anxiety", and "Sports Psychology". Five hundred eighteen articles were obtained, which were then filtered based on inclusion and exclusion criteria, and 23 articles were analyzed. Result: The results of the analysis show a negative relationship in the moderate category between mental toughness and competitive anxiety, with rRE = -0.320 (z = -3.030; p < 0.002; 95% CI: -0.113 to -0.528). Egger's test showed no publication bias (p = 0.748 > 0.05). Conclusion: These findings suggest that increased mental toughness is negatively associated with athletes' levels of competitive anxiety. In other words, the higher an athlete's level of mental toughness, the lower their anåxiety levels during competition. This research suggests that coaches and sports psychologists are crucial to integrating psychological practices, such as goal setting, positive self-talk, and imagery, into athletes' training programs. This approach can help improve mental toughness and reduce athletes' anxiety during competition.